(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Aggression in adolescents is a current problem related to psycho-emotional state and physiological factors. The concept of mizaj in traditional medicine suggests that individual temperament influences behavioral responses. Diet also plays an important role in regulating the nervous system. Objective: To examine the impact of Mizaj temperament on aggression and gastrointestinal dysfunction, with a focus on dietary preferences based on Unani medicine principles. Methods: 212 adolescents (13.5-14.8 years old) were analyzed. Mizaj assessment by traditional diagnosis, analysis of aggression by Buss-Durkee scale, study of dietary habits Results: Correlations between mizaj, diet and level of aggression were determined. Adolescents with a particular type of mizaj (e.g., saffravium or damavium) showed increased rates of aggression, especially with magnesium, vitamin D, and omega-3 deficiencies. Conclusion: Nutritional correction and consideration of mizaj can reduce aggression in adolescents, which can be used in prevention programs.